Student Knowledge Monitoring by Teachers of Computer Technologies - Sadikov Khamid Makhmudovich; Sadikova Dilfuza Ropijonovna (Zien Journals, 2021)
This article examines the control of students’ knowledge based on computer technology. The main goal of a computer sustem for monitoring knowledge, skills and abilities of students is to identify their achievements and successes, show ways to improve them, views on creating conditionsfor
Keywords: Teacher; computer; knowledge; skills; qualifications; control; monitoring